1999
DOI: 10.1902/jop.1999.70.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A Six‐Month Comparison of Three Periodontal Local Antimicrobial Therapies in Persistent Periodontal Pockets

Abstract: Although all 3 locally applied antimicrobial systems seem to offer some benefit over scaling and root planing alone, a treatment regimen of scaling and root planing plus tetracycline fiber placement gave the greatest reduction in probing depth over the 6 months after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
74
6
8

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 32 publications
6
74
6
8
Order By: Relevance
“…An elevated antibody response to A. actinomycetemcomitans has been reported to function to eliminate the bacteria. 38) A. actinomycetemcomitans may be eliminated by a high level of antibody to A. actinomycetemcomitans in ACS. Subsequently, A. actinomycetemcomitans could not be detected in the chronic period.…”
Section: Discussionmentioning
confidence: 99%
“…An elevated antibody response to A. actinomycetemcomitans has been reported to function to eliminate the bacteria. 38) A. actinomycetemcomitans may be eliminated by a high level of antibody to A. actinomycetemcomitans in ACS. Subsequently, A. actinomycetemcomitans could not be detected in the chronic period.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14]21 Although the use of systemic antibiotics has been studied in patients with GAgP, the use of adjunctive TCF in these patients has not been reported. 1,22,23 The purpose of the present study was to compare the clinical response of local versus systemic antibiotic treatment as adjuncts to scaling and root planing in patients with generalized aggressive periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Quiryen et al suggested that CHX treatment should be re-evaluated as an adjunct to SRP periodontal therapy (Quiryen et al, 2000). While the use of antibiotics (e.g., minocycline and tetracycline) represents a possible adjunct to SRP, and local drug delivery systems can improve clinical and microbial outcomes (Williams et al, 2001), their systemic use has undesirable side effects (e.g., antibiotic resistance, pseudomembranous colitis) (Radvar et al, 1996;Kinane and Radvar, 1999). The development of alternative treatments for periodontitis thus remains an important area of current oral health care research.…”
mentioning
confidence: 99%